A daring escape [large type] - Goyer, Tricia (The London Chronicles, 2018)
Danger Closes In. Can the Children be Rescued? As the threat of World War II looms on the horizon, American Amity Mitchell is living a comfortable life abroad as a tutor in England. Life changes when an urgent telegram arrives from her brother, Andrew, summoning her to Prague. Nazi forces tighten their grip on the country, and Andrew's efforts to help Jewish children escape Czechoslovakia grow desperate. Children's lives are at risk. Amity knows she can't ignore God's call to join her brother's cause. Amity's boss, Clark, arrives in Prague, urging her to return. Soon, he too finds himself helping prepare kindertransports bound for the safety of England. With the sound of German tanks rumbling over cobblestone streets, Amity and Clark race to save innocent lives. Will their prayers for deliverance be answered? A Daring Escape is a gripping tale of hope, self-sacrifice, and the power of unrelenting love overcoming unspeakable hate.